CUSTOMER RELATIONSHIP MANAGEMENT CONCEPT IN BUILDING BRANDING LAUAK BADA BUSINESS AT MANDEH TOURISM AREA - Radius Prawiro; Novi Trisna; Annisak Izzaty Jamhur (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
The concept of CRM is a concept aimed at establishing a good relationship with the customer. The concept ofCRM appears based on the paradigm that sellers should be able to maintain the loyalty of consumers who buytheir products. The business strategies found in the CRM concept aims to increase customer satisfaction so that itcan improve consumer loyalty. In this era of digital and globalization nowadays, where information is soaccessible and enjoyed by all circles using the application Pika CRM is very helpful business people inmarketing their products, a strong brand can make it very easy to know and sell to consumers because brandingor brand users feel so very important to have. Many companies and independent business units currently dependon the brand to market the products they produce so that they can sell easily with a brand that is already knownto the community. One of the growing business units currently is a business unit of the side dish of the Mandeharea of West Sumatra's south coast. Therefore, the important role of good and interesting branding is necessaryto increase the sales of the Mandeh area side dishes at a higher price